2020
DOI: 10.3390/ijgi9110637
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Global Population Datasets: Differences and Spatial Distribution Characteristics

Abstract: Spatial data of regional populations are indispensable in studying the impact of human activities on resource utilization and the ecological environment. Because the differences between datasets and their spatial distribution are still unclear, this has become a puzzle in data selection and application. This study is based on four mainstream spatialized population datasets: the History Database of the Global Environment version 3.2.000 (HYDE), Gridded Population of the World version 4 (GPWv4), Global Human Set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Grid3 is an emerging dataset that presently provides population data for several African countries as a bottom-up model. The historic HYDE model, based on the United Nation's World Population Prospects and historical estimations from the literature [23,24], provides a time series of the human population with a spatial resolution of 10 km. These population models use a variety of ancillary data (e.g., built-up masks, land cover, land use, roads, infrastructure, services, night-time lights, topography and points of interest [7,9,25]) that assist in the spatial distribution of the population [8,25,26].…”
Section: Gridded Population Models-their Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Grid3 is an emerging dataset that presently provides population data for several African countries as a bottom-up model. The historic HYDE model, based on the United Nation's World Population Prospects and historical estimations from the literature [23,24], provides a time series of the human population with a spatial resolution of 10 km. These population models use a variety of ancillary data (e.g., built-up masks, land cover, land use, roads, infrastructure, services, night-time lights, topography and points of interest [7,9,25]) that assist in the spatial distribution of the population [8,25,26].…”
Section: Gridded Population Models-their Strengths and Limitationsmentioning
confidence: 99%
“…Commonly used methods include the root mean square error (RMSE), mean absolute error (MAE) and mean absolute percentage error (MAPE) [9,39]. Table 2 summarizes five common causes of errors: the spatial heterogeneity of the environment (e.g., variations in population densities) [23,40]; the quality of census data (e.g., temporal and spatial resolution) [32,41]; the quality of ancillary data [42] (e.g., reliance on coarse-resolution night-time light data); the scale effect and temporal mismatch increase uncertainty (e.g., differences in data availabilities) [8]; and differences in regional and local characteristics (e.g., differences in the urbanization rate). Most HIC countries have a relatively slow rate of population growth and a more stable settlement pattern than LMICs, impacted by uncontrolled urbanization (e.g., slums).…”
Section: Gridded Population Models-their Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, it would not be surprising that researchers make informed decisions according to their needs. Usually, empirical research at the country level collects and utilizes population counts from census and/or yearbooks as actual value to assess the accuracy of gridded population datasets [18,[21][22][23][24]. For example, Bai et al [21] evaluated the data accuracy of the GPW, Global Rural-Urban Mapping Project (GRUMP), Worldpop, and China 1 km Gridded Population (CnPop) datasets in China, and found that the Worldpop had the highest estimation accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…This is often a challenge to assess, as where detailed, recent population data exist, often it is the input to the models, leaving a lack of independent data to compare against. Studies using detailed census data ( Bustos et al, 2020 , Chen et al, 2020 , Fries et al, 2021 , Yin et al, 2021 ), as well as cross-validation ( Reed et al, 2018 , Stevens et al, 2015 , Stevens et al, 2020 ) have tried to assess how well different models replicate population numbers and distributions at the scale of available data, and unsurprisingly those more complex models using detailed settlement mapping and range of covariates tend to do best. However, multiple trade-offs exist in the production of such datasets that depend on aspects such as input data availability, geographical extent, temporal range, spatial resolution, intended use and user needs.…”
Section: Modelled Small Area Population Estimatesmentioning
confidence: 99%